A cognitive integration of rationalist and idealist theories on poetic genesis and some of its main concepts: inspiration, unconscious, ecstasy, muses and physis - García-Valero, Benito (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
The origin of poetry and of poetic texts has been controversial since ancient times. The ancient Western literary theory distinguished two big groups of thesis to explain poetic activity: idealism, in line with the Platonic tradition, and rationalism, in line with Aristotle’s thought. The former explains poetry by resorting to divine revelation, epiphany, and ecstasy, or, in the non-religious accounts, poetry is understood as an expression of the poet’s inner world. The latter explains poetry as the result of natural gifts and talents in the human being, which creates the best poems only after a process of conscious elaboration. In the idealist tradition the body plays a fundamental role, whereas the mind is the main protagonist for rational theories. This paper combines both traditions under cognitive perspectives, and applies a concept of consciousness as a continuum between body and mind processes, or between conscious and unconscious processes, in an attempt to synthetize two aspects of the human being (body and mind) since both have equal importance in poetic activity.